The Entire March Family Trilogy - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Entire March Family Trilogy" by William Dean Howells is a collection of novels written during the late 19th century. The first part, "Their Wedding Journey," introduces the characters Basil and Isabel March, who embark on a wedding trip filled with reflections on love, societal norms, and the American landscape, following a long courtship marked by both separation and renewal. At the start of the book, the narrative unfolds with the couple preparing for their wedding journey after years of a complicated relationship. They have decided to travel modestly, choosing to avoid the public attention of a traditional honeymoon. Their journey begins during a powerful summer storm, which serves as a backdrop for their intimate conversations, foreshadowing the trials and tribulations they will encounter. As they navigate the bustling environment of travel, their dynamic reflects both a deep connection and the shared vulnerabilities of newly married life. Through lively discussions, humorous banter, and poignant observations, the opening sets the tone for a deeper exploration of the complexities of marriage, individual identity, and societal expectations within the American context. (This is an automatically generated summary.)
Their Wedding Journey -- A Hazard Of New Fortunes -- Their Silver Wedding Journey.
Release date is 2004-10-23
Produced by David Widger
Keywords: Fiction; Literature -- Collections